Impact of perineal pain and delivery related factors on interference with activities of daily living until 1 month postpartum: A longitudinal prospective study - Akiko Yamada; Yuki Takahashi; Yurika Usami; Koji Tamakoshi (BMC, 2024)
Abstract Background Interference with activities of daily living can negatively impact maternal practices both physically and psychologically. This study aimed to explore the patterns of interference with activities of daily living and perineal pain among Japanese women until 1 month postpartum. Furthermore, we aimed to describe how both perineal pain and delivery-related factors were associated with interference with activities of daily living. Methods This study was part of a larger prospective longitudinal study conducted at five maternity hospitals in Japan. The participants were 293 women who had full-term vaginal deliveries and singleton infants. Participants self-evaluated their perineal pain and interference with activities of daily living using a 100 mm visual analogue scale and 'behaviour that interferes with daily life scale' at day 1, day 5, and 1 month postpartum. We used a linear mixed model to calculate the fixed-effects parameter estimates and their 95% confidence intervals. Interference with activities of daily living, which included difficulty sitting, difficulty moving, and difficulties with excretion and cleanliness, were set as the dependent variables. Results The final analysis included 184 participants with a mean age of 31.5±4.5 years. Perineal pain and the three sub-scales of interference with activities of daily living reduced from day 1 to 5 postpartum, and further from day 5 to 1 month postpartum (perineal pain, p<0.01, p<0.01; difficulty sitting, p<0.01, p<0.01; difficulty moving, p<0.01, p<0.01; difficulties with excretion and cleanliness, p<0.01, p<0.01). These tendencies did not change, even adjusted for independent variables using a mixed model. In the mixed model for follow-up data, perineal pain was a significantly and positively associated with three sub-scales of interference with activities of daily living, even after adjusted for perineal injury and episiotomy. Conclusions Positive relationships were observed between perineal pain and interference with activities of daily living until 1 month postpartum, although both reduced. To promote maternal role attainment through child-rearing since early postpartum, midwives should pay additional attention to mothers' perineal pain as it could negatively affect their daily life and child-rearing.